Perencanaan Dinding Penahan Tanah Type Gravitasi di Perumahan De Salvia Kelurahan Tanjungrejo Kecamatan Sukun Kota Malang - Zhohirin, Zhohirin; Suhudi, Suhudi; Sulistyani, Kiki Frida (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2018)
ABSTRACT Soil as construction material as well as the foundation of a construction land or structures such as dams, embankments, retaining walls, buildings and bridges. In every construction requires a specific requirement in terms of both strength and economically. This study aimed to analyze and plan for a stable retaining wall on the stability of the shift, the overthrow and the carrying capacity by using Gravity Type On Housing Da Salvia District Sukun Malang City. Calculation of earth pressure calculated using Rankine theory. Stability Analysis Results Retaining Walls with Gravity Type Dimensions: Width top (B1) 0.30 m, base width (B2) 2.00 m and a total height (H + D) 6.00 m, which then did not secure the stability of the overthrow ( 0.4 1.5). Results Budget Plan (RAB) in the calculation of total fees earned USD 241.774.018, the cost of any work (m3) Rp 1.557.170,116, job retention costs (m) USD 4.395.891,236 Keywords ; Analysis ; Dimensional ; Gravity Type Retaining Walls.